(untitled) (Bangladesh Journal of Child Health, 2010)
Objective: To investigate the efficacy of subcutaneous versus oral methotrexate in patients with Juvenile Idiopathic Arthritis (JIA) according to ACR 30 improvement criteria. Design: Prospective control trial (Parallel design) study. Setting: This study was carried out in the department of Paediatrics, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, during the period from September 2006 to April 2008. Patients: A total of 40 patients participated in the study. They were divided in 2 equal groups (Group A and Group B) alternatively matching with age, sex, and subtypes of the disease. Methotrexate was given orally in group A patients and subcutaneously in group B patients. Results: Amomg the core set variables active arthritis had the highest percentage of improvement in both the groups and laboratory criteria (ESR) showed lowest improvement. According to ACR-30 criteria, improvement rate was higher in the subcutaneous group than oral group (85% versus 65%). Side effects of MTX were also less in subcutaneous group than oral group. Conclusion: From this study it may be concluded that the efficacy of subcutaneous MTX is more than oral MTX in JIA patients. Key words: Subcutaneous; oral; methotrexate; juvenile idiopathic arthritis. DOI: 10.3329/bjch.v33i1.5671 Bangladesh Journal of Child Health 2009; Vol.33(1): 22-26